Money or honor ; A domestic problem ; On our own [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
The secretary of Energy's pronouncement that the government was considering a settlement agreement with Westinghouse ; the maker of Bataan Nuclear Power Plant. Enactment of "Maids bill" by Congress gives housewives open complaint about the deteriorating quality for household helpers. McKintosh Production on Les Miserables staged in the Philippines by Filipino performers.
Money or honor (18 min.) -- A Domestic problem (11 min.) -- On our own (18 min.)
VHS.
Keywords: Hugo, Victor Marie Conte, 1802-1885. -- Adaptations; Bataan Nuclear Power Plant; Atomic power plants -- Philippines; Wages -- Minimum wage -- Philippines; Musicals